The emerging roles of eRNAs in transcriptional regulatory networks - Mousavi, Kambiz (Landes Bioscience, 2014)
Following reports by ENCyclopedia Of DNA Elements (ENCODE; GENCODE) Consortium and others, it is now fairly evident that the majority (70–80%) of the mammalian genome has the potential to be transcribed into non-protein-coding RNAs (ncRNAs). Critical to our understanding of genetic processes is the mechanism by which ncRNAs exert their roles. Accordingly, ncRNAs are shown to regulate the expression of protein-coding loci (i.e., genes) at the transcriptional as well as post-transcriptional stages. We recently reported on a widespread transcription at the DNA enhancer elements in myogenic cells. In our study, we found certain enhancer RNAs (eRNAs) regulate chromatin accessibility of the transcriptional machinery at loci encoding master regulators of myogenesis (i.e., MyoD/MyoG), thus suggesting their significance and site-specific impact in cellular programming. Here, we examine recent discoveries pertinent to the proposed role(s) of eRNAs in regulating gene expression. We will highlight consistencies, discuss confounding observations, and consider a lack of critical information in a way to prioritize future objectives.